Two new species of Sinacrulia Shavrin, 2023 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) from Nepal and Myanmar - Shavrin, Alexey V. (Zootaxa, 2025)
Two new species of the genus Sinacrulia Shavrin, 2023, previously known only from one described and one unnamed species from China (Yunnan), are described and illustrated: S. monticola sp. nov. (northeastern Nepal: Koshi) and S. schillhammeri sp. nov. (Myanmar: Chin State). Both new species are closely related to the former species (S. forteripunctata Shavrin, 2003), and can be distinguished from it by details of the morphology of the antennae, pronotum, elytra, and the aedeagus. The distribution of the genus is mapped, and a key to all known species is provided.